Eco-Calligraphy: Utilizing Cardboard Waste As A Medium For Edupreneurship At Mi Al-Hidayah - Lailatul Lutfiyah; Risa Igrit Alita (Islamic Journal of Teaching and Learning, 2026)
Background: This study aims to describe the utilization of cardboard waste as eco-calligraphy media in entrepreneurship-based learning at MI Al-Hidayah. The study is motivated by the limited creativity of students in processing waste materials and the lack of learning activities that integrate artistic, economic, and environmental values in madrasa education. Objective: This study aims to describe the utilization of cardboard waste as eco-calligraphy media in entrepreneurship-based learning at MI Al-Hidayah. Method: This study employed a descriptive qualitative approach involving 18 sixth-grade students of MI Al-Hidayah over a one-month period. Data were collected through observation, interviews, and documentation to obtain an in-depth understanding of the learning process and outcomes. Findings and Implications: The findings indicate that transforming cardboard waste into eco-calligraphy enhances students' creativity, independence, and skills in producing works with aesthetic and economic value. In addition, this activity increases students' awareness of environmental sustainability through recycling practices and responsible waste management. The implementation of eco-calligraphy also supports the integration of spiritual, social, and entrepreneurial values in learning. Conclusion: The use of cardboard waste as eco-calligraphy media is an effective alternative for developing entrepreneurship-based learning in madrasa settings and has the potential to support sustainable and creative learning practices in broader educational contexts.